Neuro-hormonal regulation of aqueous humor dynamics as the basis of glaucoma pharmacotherapy. Part II – Aqueous humor outflow - Terelak-Borys, Barbara; Liberek, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The aim of this article is to present current opinion on aqueous humor dynamics regulation and antiglaucoma drugs mechanisms of action. Pharmacotherapy of glaucoma is based mainly on neuro-hormonal processes controlling aqueous humor dynamics. Systemic hormones as well as local hormones and autonomic nervous system mediators are involved in the processes of aqueous humor formation and drainage. Antiglaucoma medications act mainly through activation or inhibition of these systems’ receptors, helping to decrease aqueous humor production or improve aqueous humor outflow. In this article (part 2) we describe two groups of antiglaucoma medications (parasympathicomimetics, prostaglandin analogues), inhibiting the aquoeus humor outflow and mechanisms of their hypotensive effect in the eye.